The Koromong Art as a Medium for the Expression of Cultural Identity and Spirituality for the Outer Baduy Community - Hudaepah Hudaepah; Dewi Haryaningsih; Budi Kurniawan (Institute of Multidisciplinary Research and Community Service, 2026)
Koromong is a traditional performing art of the Outer Baduy community in Lebak Regency that has been preserved despite increasing exposure to modernization. However, growing interaction with the outside world has the potential to reshape the cultural and spiritual values embedded in this tradition. This study examines Koromong as a medium for expressing cultural identity and spirituality and explores its role in preserving the local wisdom of the Outer Baduy community. Specifically, the research investigates the meanings, functions, and symbolic values of Koromong within the community's social, cultural, and religious life. It analyzes its role in sustaining collective identity and spiritual beliefs amid ongoing social change. This study adopts an ethnographic approach that views artistic practices as integral to the community's cultural system. Data were collected through participant observation, in-depth interviews, documentation of artistic performances, and field recordings. To enhance the credibility of the findings, data were triangulated across multiple sources and methods, including observations, interviews, and documentary evidence. The data were analyzed using a descriptive-interpretive approach to identify the symbolic meanings, social functions, and cultural values represented in Koromong performances. The findings demonstrate that Koromong serves not only as a form of folk entertainment but also as a ritual and spiritual practice that symbolizes the relationship between humans, nature, and Sang Hyang Karesa. Its musical rhythms, poetic expressions, and ceremonial sequences represent the cultural identity of the Outer Baduy community while providing a space for collective spiritual expression. Furthermore, each instrument in the Koromong ensemble embodies symbolic meanings associated with cosmology, social order, and communal solidarity. As a result, Koromong functions as an important medium for transmitting cultural values across generations and strengthening cultural resilience, enabling the Outer Baduy community to preserve the balance between tradition, belief, and social life in the face of modernization. Keywords: Spirituality, Cultural identity, The Koromong art, Outer Baduy community.